Last Decade of the Recollects in San Carlos Borromeo Parish, Negros Occidental (1965-1975) - Romanillos, Emmanuel Luis A. (Philippine Social Science Journal, 2020)
The controversial cession of San Carlos Borromeo Parish in 1975 by the Augustinian Recollects to the diocesan clergy was significant. Unknown by the present generation, the story is recalled in detail forty-five years after. Rich in primary sources and personal interviews with Recollects and diocesan priests, both protagonists, and eyewitnesses were utilized. The narrative objectively recounts the Recollect ministry in San Carlos. It then focuses on the diocesan consultors’ meeting in October 1974 that sanctioned the takeover despite the lack of priests, the uninformed Recollect superiors’ vicarial meeting on the reshuffle of curates in November 1974, and the persistent takeover rumors in San Carlos since October 1974. The official cession—that included Calatrava and Barangay Quezon parishes—happened on 6 January 1975. Reasons are revealed and discussed. In retrospect, the early beginnings of San Carlos and its creation as a diocese in 1988 have reminisced. Highlighted is Bishop Epifanio Surban’s heartfelt gratitude for the Recollect evangelization effort.